Flexible, thin films of graphene–polymer composites for EMI shielding. (28th March 2017) - Jan, Rahim; Habib, Amir; Akram, Muhammad Aftab; Ahmad, Imtiaz; Shah, Attaullah; Sadiq, Muhammad; Hussain, Akhtar
Abstract: Liquid-phase-exfoliated, pristine graphene nanosheets (GNSs) are dispersed in thermoplastic polyurethane (TPU) to obtain free-standing conducting composite films. The composites are tested for electromagnetic interference (EMI) shielding applications in the X-band (8–12 GHz). A constant increase in the electromagnetic attenuation is observed as a function of GNS loading (0–0.12 V f ). The EMI shielding effectiveness of about 1 dB for the neat polymer is enhanced to about 14 dB at 0.12 V f GNS as the electromagnetic energy is dissipated due to the GNS conducting network formed inside. Conducting behavior of GNS–TPU composites is confirmed by electrical conductivity measurements along with cyclic voltammetry as the band gap is reduced with a graphene increment. Scanning electron microscopy predicts a homogeneous dispersion of GNS inside composites. For such thin composite films (0.03–0.05 mm), the EMI shielding effectiveness is considerable.